THE ROLE OF THE BALANCE OF PAYMENTS IN ECONOMIC GROWTH - Musаbekоv Sherаli Nаzаrаli о’g’li (University Research Base, 2024)
This thesis examines the intricate relationship between a nation's balance of payments (BoP) and its economic growth. It delves into the theoretical underpinnings of the BoP and its various components, analyzing how they influence a country's growth trajectory. The thesis explores both the positive and negative aspects of BoP positions (surpluses and deficits) on economic activity. It critically evaluates different schools of thought on the BoP's role in growth, acknowledging both its potential as a driver and its limitations as a sole determinant. The analysis incorporates real-world examples to illustrate the multifaceted nature of this relationship. Finally, the paper concludes by emphasizing the importance of considering a holistic approach to economic growth that integrates BoP dynamics with domestic economic policies and external factors.